Turkish League Against Rheumatism Consensus Report: Recommendations For Management of Axial Spondyloarthritis - Gülcan GÜRER; Gürkan YILMAZ; İsmihan SUNAR; İlhan SEZER; Aylin REZVANİ; Sumru ÖZEL; Erhan ÖZDEMİREL; Meltem Alkan MELİKOĞLU; Ömer KURU; Hilal KOCABAŞ; Taciser KAYA; Ece KAPTANOĞLU; et al. (Archives of Rheumatology, 2018)
Objectives: This study aims to update 2011 Turkish League Against Rheumatism SpondyloArthritis Recommendations, and to compose a national expert opinion on management of axial spondyloArthritis under guidance of current guidelines, and implantation and dissemination of these international guidelines into our clinical practice. Materials and methods: A scientific committee of 28 experts consisting of 14 rheumatologists and 14 physical medicine and rehabilitation specialists (one of them also has an immunology PhD) was formed. The recommendations, systematic reviews, and meta-analyses including pharmacologic and non-pharmacologic treatment were scrutinized paying special attention with convenient key words. The draft of Turkish League Against Rheumatism opinion whose roof consisted of international treatment recommendations, particularly the Assessment of SpondyloArthritis International Society/European League Against Rheumatism recommendations was composed. Assessment of level of agreement with opinions by task force members was established through the Delphi technique. Voting using a numerical rating scale assessed the strength of each recommendation. Results: Panel compromised on five basic principles and 13 recommendations including pharmacological and nonpharmacological methods. All of the recommendations had adequate strength. Conclusion: Turkish League Against Rheumatism expert opinion for the management of axial spondyloArthritis was developed based on scientific evidence. These recommendations will be updated regularly in accordance with current developments.